Empowerment of Household Woman Group Through Hydroponic Cultivation Using Wick System in The Lingkungan XV Tanjung Mulia Medan - Anggraini, Novita; Syahputra, OK Hasnanda; Hartono, Rudi; Samsuri (Talenta Publisher, 2022)
Community service activity was conducted in July-October 2021. The main event was held on September 4, 2021, and attended by around 33 participants divided into two sessions due to the Implementation of Community Activity Restrictions (PPKM). The core activity begins with explaining the history and understanding of hydroponics, the advantages of hydroponics, planting media and potting media, types of hydroponics, stages of hydroponic vegetable cultivation, manufacture of vegetable pesticides, and harvesting. The direct practice of the activity begins with cutting Rockwool, media preparation, and sowing mustard and kale seeds. Transplanting do when the seedlings are 7-10 days old, and after three weeks of transplanting, we can do the harvesting. Each participant filled out a questionnaire for the evaluation. Based on the questionnaire review, most participants had heard of the hydroponic system but had never received the training. Furthermore, after receiving this training, most participants understood the hydroponic system and tended to agree that hydroponic plant cultivation is easy to do and can be a business opportunity. Meanwhile, in terms of costs, participants tend to state that hydroponic systems require high costs.